Associations between maternal iron supplementation in pregnancy and offspring growth and cardiometabolic risk outcomes in infancy and childhood. - Clive J Petry; Laurentya Olga; Ieuan A Hughes; Ken K Ong (PLoS ONE)
It was previously observed that maternal iron supplementation in pregnancy was associated with increased offspring size and adiposity at birth, possibly mediated through increased risk of gestational diabetes. In this study we investigated potential long-term associations of maternal iron supplementation in pregnancy with offspring growth in infancy, and growth and cardiometabolic risk factors in mid-childhood to seek evidence of nutritional programming. Using a nested case-control format, markers of growth and adiposity were measured at 3, 12 and 24 months of age in 341 infants from the Cambridge Baby Growth Study whose mothers supplemented with iron in pregnancy and 222 infants whose mothers did not. Measures of growth, glucose tolerance (using a 30 minute 1.75 g glucose/kg body weight oral glucose tolerance test), insulin sensitivity (HOMA IR) and blood pressure were collected in 122 and 79 of these children, respectively, at around 9.5 years of age. In infancy adiposity-promoting associations with maternal iron supplementation in pregnancy were evident at 3 months of age (e.g. mean difference in skinfold thickness: β = +0.15 mm, p = 0.02, in n = 341 whose mothers supplemented versus 222 that did not; waist circumference: β = +0.7 cm, p = 0.04, in n = 159 and 78, respectively) but differences lessened after this time (e.g. 3-12 month change in mean difference in skinfold thickness: β = -0.2 mm, p = 0.03, in n = 272 and 178, respectively). At ~9.5 years of age children whose mothers supplemented with iron in pregnancy had lower mean arterial blood pressures (β = -1.0 mmHg, p = 0.03, in n = 119 and 78, respectively). There were no apparent differences in markers of growth or other cardiometabolic factors. These results suggest that most of the associations of maternal iron supplementation in pregnancy on growth and adiposity evident at birth disappear during infancy, but there may be some evidence of long-term nutritional programming of blood pressure in mid-childhood.